Investigating the Empowerment of the Physically-Handicapped People and Its Related Factors: A Cross-Sectional, Analytical Study in Kohgiluyeh and Boyer-Ahmad Province in 2015 - Vahid Dastyar; Asghar Mohammadi (University of Social Welfare and Rehabilitation Sciences, 2019)
Objective Empowerment is a process that helps the physically-handicapped people to break the poverty loop, achieve self-reliance and self-sufficiency, and join the mainstream of life. This study aimed to investigate the empowerment (sense of meaningfulness, effectiveness, autonomy, self-efficacy and sense of security, and their related factors) of the physically-handicapped people (motor, visceral and sensory disabilities) under the support of Welfare Organization of Kohgiluyeh and Boyer-Ahmad Province in 2015. Materials & Methods The research method was survey-based; a type of cross-sectional and analytical method. The data collection tool was a researcher-made questionnaire (including four demographic questions (level of education, gender, disability type, and age) and 46 research-specific questions (10 questions about social trust, 9 questions about social participation, 8 questions about sports activity, 4 questions about sympathy behaviors and 15 questions about empowerment of people with disabilities) with 5-point rating Likert-type scale. The statistical population comprised all the physically-handicapped people (motor, visceral, and sensory disabilities) who were under the support of Welfare Organization of Kohgiluyeh and Boyer-Ahmad Province, Iran. They comprised about 10189 people in each city. A total of 370 subjects were selected as a sample using Kokaran formula and then randomized sampling was used between eight cities of Kohgiluyeh and Boyer-Ahmad Province. Therefore, in the first stage, 8 cities were selected. In the second stage, the physically-handicapped people of each city were selected with the help of the welfare organization of the city. In the third stage, a group of physically-handicapped people was randomly selected. In the final stage, they were visited personally. In this study, the validity of the questionnaire was tested through content validity, i.e. by referring to common sense, expert judges, books and related subjects. In other words, a completed questionnaire was delivered to counsellor professor and 10 experts and professors in the field of Methodology, Psychology, and Sociology. Then, their comments and views about indices, reagents and research subjects were taken and the final questionnaire was compiled. In order to assess the reliability of the questionnaire before its final completion, 40 questionnaires were prepared and its alpha values were found using Cronbach method as 0.84 for the empowerment of the people with disabilities, 0.72 for the social trust, 0.77 for the social participation, 0.85 for the sports activity, and 0.90 for the sympathy behaviors. The data analysis was done using descriptive statistics (frequency, percentage, mean, standard deviation, skewness and kurtosis) and inferential statistics (Pearson correlation coefficient tests, variance analysis, t test for two Independent samples, multivariate regression, and path analysis) in SPSS V. 21. Results Results of the Pearson correlation coefficient analysis indicate a significant relationship between the social trust (with three dimensions of interpersonal trust, generalized trust and institutional trust), social participation (with two dimensions of formal and informal participation) and sports activities (with two dimensions of the promotion of physical and mental health) with the empowerment of the physically-handicapped people (P<0.001). There was no relationship between the variables of age (P=0.418) and sympathy behaviors (P=0.395) with the empowerment of the physically-handicapped people. According to the results of t test in terms of the demographic characteristics of the physically-handicapped people, there was no significant difference between gender and empowerment of the physically-handicapped people (P=0.756). Based on the results of the variance analysis test in terms of the demographic characteristics of the physically-handicapped people, there was no significant difference between the type of disability and empowerment of the physically handicapped people (P=0.174). However, there is a significant difference between the education level and empowerment of the physically handicapped people (P<0.001). People with disability, who were highly educated, had higher empowerment ability. The results of regression test analysis showed that the most important variables affecting the empowerment of the physically-handicapped people were institutional trust (β=0.327), environmental trust (β=0.133), informal participation (β=0.132) and educational level (β=0.118). In addition, the variance of the empowerment of the physically-handicapped people was affected by 28% than the significant independent variables existed in the model. Among the effective variables, social participation had the highest influence on the empowerment of the physically-handicapped people and then social trust, education level and sports activities in the descending order. Conclusion The study results indicate that four variables of age, gender, type of disability and sympathy behaviors failed to explain the changes of the empowerment of the physically-handicapped people, but four variables of social trust, social participation, sports activities and educational level could explain the changes of the empowerment of the physically-handicapped people. It is recommended that research studies about the empowerment of the physically-handicapped people should be continued in order to better understand the facilitators and barriers to the empowerment of the physically handicapped.